Структурні та функціональні особливості кулінарної лексики в британському телешоу The Great British Bake Off - Лопатюк, Наталія; Молдован, Віта (Видавничий дім «Гельветика», 2020)
The aim of the presented article is a thorough investigation of structural and functional characteristics of the culinary vocabulary selected from the on-line scripts of the British television baking competition The Great British Bake Off. Thus, a modern culinary show may be defined as a new genre of a TV programme on a gastronomic topic, with its most important peculiarities being entertainment, some elements of a reality show and competition, and a shifted emphasis from the cooking process itself to the conflicts arousing among the contesters. In the course of our investigation, the analyzed vocabulary has proved to consist chiefly of nouns, both simple and compound ones, which account for about two-thirds of the material under study. The latter have either the NN (one word) or N+N (written separately) structure. Also, the outcomes show that nominal word combinations build a little less than a third of the culinary vocabulary; verbs, adjectives as well as their combinations turned to be infrequent. It is also worth mentioning that the material under investigation includes both neutral words and professionalisms mainly belonging to haute cuisine. In this way, cake, pie, and their ingredients nominations are characterized by the most frequent application. Moreover, they are often derived from proper names denoting the place of their origin (Gruyère cheese), their inventor/creator (Clementine, frangipane), or just a celebrity of those times (Leibniz). In linguistics, the words of such a type are referred to as eponyms, i.e. common nouns originating from proper ones. The study also shows that groups of lexemes denoting dishes as well as cooking and storing equipment, cooking processes, and attributes display their rare use. The latter is often expressed by nouns in the function of attributes meaning either the main ingredient of the dish or its shape or an event the pastry is dedicated to. Finally, it should be mentioned that clusters of fruit, spices, and meat nominations are seldom used to denote stuffing, the same low frequency being displayed by lexemes for some kinds of alcohol used to soak the dough.
Подана стаття присвячена дослідженню структурних та функційних характеристик кулінарної лексики, виділеної зі скриптів британського кулінарного телешоу The Great British Bake Off. Сучасне ку- лінарне шоу – це новий жанр програм гастрономічної тематики, характерними особливостями якого є ви- довищність, елементи реаліті-шоу та конкуренції, зсув акцентів з приготування їжі на показ конфліктних відносин між учасниками. У ході дослідження було встановлено, що аналізована кулінарна лексика майже повністю побудована на іменниковій основі. Також вона складається як з нейтральної лексики загально- го вжитку, так і в більшій мірі запозичених слів вузького вжитку, обмеженого переважно високою кухнею. Найчастіше вживаються назви тортів, пирогів та їхніх інгредієнтів. Часто ці назви походять від власних назв на позначення місця їх виникнення, їхнього винахідника або просто відомої особи того часу або міста.
Keywords: culinary vocabulary; TV show; structural peculiarities; functional characteristics; eponyms.